(untitled) (Nigerian Journal of Technology, 2018)
Effective project planning in Magnetic Resonance Imaging (MRI) machine installation takes into consideration several factors including Time, Cost, Quality and Risk which are essential but conflicting factors that affect projects. These critical factors should be optimized in all projects especially those in Low and Medium Income Countries (LMIC) with limited resources and inadequate investment in medical facilities and equipment. The main objective of this study was to develop an optimization model for fuzzy Time-Cost-Quality-Risk Trade-off (TCQRT) problem for MRI machine installation project. The model was solved by Multiobjective Genetic Algorithm (MOGA) and the solutions ranked using the Technique for the Order of Preferences by Similarity to Ideal Solution (TOPSIS). The results indicate a trade-off relationship exists among time, cost, quality and risks. http://dx.doi.org/10.4314/njt.v37i2.13